A Diagnostic Nomogram for Early Prediction of Post-Infectious Bronchiolitis Obliterans in Severe Pneumonia - Yan S; Sun C; Jiang K (Dove Medical Press, 2023)
Silei Yan, Chao Sun, Kun Jiang Department of Respiratory Medicine, Shanghai Children's Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People's Republic of ChinaCorrespondence: Kun Jiang, Department of Respiratory Medicine, Shanghai Children's Hospital, School of Medicine, Shanghai Jiao Tong University, 355 Luding Road, Shanghai, 200062, People's Republic of China, Tel +86 021-62475568, Email jkjk_032@163.comObjective: The study aimed to set up and validate a predictive nomogram for post-infectious bronchiolitis obliterans in severe pneumonia.Methods: We retrospectively analyzed data of 228 patients diagnosed with severe pneumonia and constructed a prediction nomogram. The least absolute shrinkage and selection operator (LASSO) regression model was utilized to optimize the selection of features for the clinical characteristics of post-infectious bronchiolitis obliterans. Individual nomograms of bronchiolitis obliterans incorporating clinical factors were developed using the multivariate logistic model. The C-index, calibration plot, and decision curve analysis were used to verify the calibration, discrimination, and clinical utility. The bootstrapping method was used for the internal validation of the model.Results: Predictors in the individualized predictive nomogram included age of patients (odds ratio [OR], 0.994; 95% confidence interval; [CI], 0.990- 0.998), length of stay (OR, 1.043; 95% CI: 1.015- 1.073), mechanical ventilation (OR, 1.865; 95% CI: 1.236- 2.817), human adenoviral infection (OR, 1.671; 95%, CI: 1.201- 2.326), and the level of interleukin (IL)-2 (OR, 0.947; 95% CI: 0.901- 0.955). The model discriminated reasonably well, with a C-index of 0.907 (C-index, 0.888 and 0.926) with good calibration and internal validation, which was not statistically significant by the Hosmer-Lemeshow test (P = 0.5443). Decision curve analysis showed that nomograms were useful in clinical settings.Conclusion: In this study, a model was developed and presented as a nomogram with relatively good accuracy to help clinicians accurately and early diagnose post-infectious bronchiolitis obliterans in children with severe pneumonia.Keywords: bronchiolitis obliterans, severe pneumonia, child, risk factors